IMPACT OF DAMAGE OF WINTER GRAIN WHEAT BY THE CORN BUG (EURYGASTER INTEGRICEPS PUT.) ON THE CROP AND GRAIN QUALITY - Chaika, T.; Barabolia, O. (Scientific Progress & Innovations, 2022)
Today's challenges require ensuring the yield and quality of wheat grain as the main food crop for the food security of Ukraine and the countries of the world. Every year, the reasons for the lack of harvest of cereal grain crops and the deterioration of their quality are the influence of pests, especially the corn bug. The purpose of the article is to study the yield and physical qualities of the Ukrainka Poltavska soft winter wheat grain depending on the degree of damage by the corn bug (Eurygaster integriceps Put.). Soft winter wheat of the Ukrainka Poltavska variety was grown on the experimental field of the Poltava State Agrarian University in the conditions of the forest steppe. The soil of the experimental site corresponded to the following characteristics: dark gray, gilded, dusty-heavy loamy by mechanical composition, humus content in the arable layer – 3.77–3.93 %, pH=5.8–6. Quality research was carried out in the Scientific Research Laboratory of Grain Quality named after H. P. Zhemela using appropriate equipment, dishes, and reagents. The results of the research indicate the negative impact of damage to winter wheat of the Ukrainka Poltava variety by the harmful shell bug on its yield and grain quality. It was established that an increase in the degree of grain damage up to 25.3 % harmed yield and quality indicators: yield decreased by 10 %, the weight of 1000 grains – by 10.1 %, nature – by 6 %, vitrification – by 35.2 % compared to the corresponding indicators of healthy grain. The conducted correlation analysis showed the existence of a very close negative relationship between grain damage by a harmful beetle and yield indicators (r=-0.9839), the weight of 1000 grains (r=-0.9840), nature (r=-0.9888), and vitrification (r=-0.9975). Regression analysis proved the dependence of the average value of each of the indicators on the degree of grain damage (x) and the weight of 1000 grains (y): yield – Y=0.323–0.0008x+1.1476y; grain types – Y=1031.5972–2.8285x–5.2304y; vitreous grain - Y=101.0462–1.346x–0.2495y.